The NHLBI-Sponsored Consortium for preclinicAl assESsment of cARdioprotective Therapies (CAESAR). Issue 4 (13th February 2015) - Jones, Steven P.; Tang, Xian-Liang; Guo, Yiru; Steenbergen, Charles; Lefer, David J.; Kukreja, Rakesh C.; Kong, Maiying; Li, Qianhong; Bhushan, Shashi; Zhu, Xiaoping; Du, Junjie; Nong, Yibing; et al.
<x xml:space="preserve">Abstract</x> Rationale: Despite 4 decades of intense effort and substantial financial investment, the cardioprotection field has failed to deliver a single drug that effectively reduces myocardial infarct size in patients. A major reason is insufficient rigor and reproducibility in preclinical studies. Objective: To develop a multicenter, randomized, controlled, clinical trial-like infrastructure to conduct rigorous and reproducible preclinical evaluation of cardioprotective therapies. Methods and Results: With support from the National Heart, Lung, and Blood Institute, we established the Consortium for preclinicAl assESsment of cARdioprotective therapies (CAESAR), based on the principles of randomization, investigator blinding, a priori sample size determination and exclusion criteria, appropriate statistical analyses, and assessment of reproducibility. To validate CAESAR, we tested the ability of ischemic preconditioning to reduce infarct size in 3 species (at 2 sites/species): mice (n=22–25 per group), rabbits (n=11–12 per group), and pigs (n=13 per group). During this validation phase, (1) we established protocols that gave similar results between centers and confirmed that ischemic preconditioning significantly reduced infarct size in all species and (2) we successfully established a multicenter structure to support CAESAR's operations, including 2 surgical centers for each species, a Pathology Core (to assess infarct size), a Biomarker Core (to measure plasma cardiac troponin levels), and a Data Coordinating Center—all with the oversight of an external Protocol Review and Monitoring Committee. Conclusions: CAESAR is operational, generates reproducible results, can detect cardioprotection, and provides a mechanism for assessing potential infarct-sparing therapies with a level of rigor analogous to multicenter, randomized, controlled clinical trials. This is a revolutionary new approach to cardioprotection. Importantly, we provide state-of-the-art, detailed protocols ("CAESAR protocols") for measuring infarct size in mice, rabbits, and pigs in a manner that is rigorous, accurate, and reproducible.